The Bebop Revolution in Malaysia / Danial Kordy - Kordy, Danial (Faculty of Music, 2016)
The main aim of this thesis was to study the Revolution of Bebop in Malaysia. The paperwork includes information of the Bebop Revolution in Malaysia. This study is performed to measure the revolution of bebop in Malaysia. To achieve this, data has been collected by research from an interview from well-known musician in Malaysia, books, online journal and peer's self-thoughts. The paper analyzes the overall factor that happened before, during the rise of bebop to the downfall of bebop. Through researcher's own experiences during three-year studies for Bachelor's Degree in UiTM, the researcher has involved in searching knowledge about bebop. In researcher's own hypothesis, Malaysian need to be open about different type of music not just pop music or what's trending now, for us to evolve our thoughts into a new we must learn to accept. Thus, using all the information received, the researcher will design interview questions based on the issues related to the topic.